Subjective well-being patterns in older men and women without someone to confide in: a latent class analysis approach - Meng, Dijuan; Sun, Chang (Frontiers in Public Health, 2024)
We would like to submit the enclosed manuscript entitled "Subjective well-being patterns in older men and women without someone to confide in: a latent class analysis (LCA) approach", which we wish to be considered for publication in "Frontiers in Public Health".We have adequate reason for submitting our manuscript. In this paper, by applying LCA, we identified three distinct subjective well-being (SWB) patterns among older adults who lacked a close confidant: the very low SWB class (32%), the medium-low SWB class (46%) and the low evaluative and high affective SWB class (22%). Participation in social activities, self-rated health and financial status, drinking alcohol and limitations in instrumental activities of daily living were found to be associated with SWB patterns. This is significant because we examined the heterogeneity of SWB within older adults without close confidants rather than treating them as a whole without distinction or focusing on their SWB at the mean. A better understanding of the SWB patterns and associated factors in older adults without close confidants would contribute to the development of health care programs tailored to the unique needs of different subgroups.